The Crucial Role of Human Resource Competency in Enhancing the Utilization of Financial Systems and the Quality of Regional Financial Reports - Bustan Ramli; Sudirman Sudirman; Hasmin Tamsah; Baso Iwang; Bahrul Ulum Rusydi (Faculty of Economics and Business Universitas Jenderal Soedirman, 2026)
This study analyzes the effect of Human Resource Competence (HRC) on the Quality of Regional Financial Reports (QFR), with Financial System Utilization (UFS) and Internal Audit Quality (QIA) as mediating variables. Grounded in the Resource-Based View, Agency Theory, and New Public Management, the study explains how human competence, system utilization, and audit quality jointly shape public financial governance. Using survey data from 199 regional financial officers in South and West Sulawesi, the analysis employs Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM–AMOS). The results show that HRC significantly improves UFS, QIA, and QFR, while both UFS and QIA act as effective mediators. Among these, QIA provides the strongest indirect effect on QFR. The findings highlight that improving regional financial reporting quality requires an integrated strengthening of human resources, financial systems, and internal audit functions.